The Multiple Roles of the Cytosolic Adapter Proteins ADAP, SKAP1 and SKAP2 for TCR/CD3 -Mediated Signaling Events - Dadwal, Nirdosh; Mix, Charlie; Reinhold, Annegret; Witte, Amelie; Freund, Christian; Schraven, Burkhart; Kliche, Stefanie (Frontiers in Immunology, 2021)
T cells are the key players of the adaptive immune response. They coordinate the activation of other immune cells and kill malignant and virus-infected cells. For full activation T cells require at least two signals. Signal 1 is induced after recognition of MHC/peptide complexes presented on antigen presenting cells (APCs) by the clonoctypic TCR (T-cell receptor)/CD3 complex whereas Signal 2 is mediated via the co-stimulatory receptor CD28, which binds to CD80/CD86 molecules that are present on APCs. These signaling events control the activation, proliferation and differentiation of T cells. In addition, triggering of the TCR/CD3 complex induces the activation of the integrin LFA-1 (leukocyte function associated antigen 1) leading to increased ligand binding (affinity regulation) and LFA-1 clustering (avidity regulation). This process is termed “inside-out signaling”. Subsequently, ligand bound LFA-1 transmits a signal into the T cells (“outside-in signaling”) which enhances T-cell interaction with APCs (adhesion), T-cell activation and T-cell proliferation. After triggering of signal transducing receptors, adapter proteins organize the proper processing of membrane proximal and intracellular signals as well as the activation of downstream effector molecules. Adapter proteins are molecules that lack enzymatic or transcriptional activity and are composed of protein-protein and protein-lipid interacting domains/motifs. They organize and assemble macromolecular complexes (signalosomes) in space and time. Here, we review recent findings regarding three cytosolic adapter proteins, ADAP (Adhesion and Degranulation-promoting Adapter Protein), SKAP1 and SKAP2 (Src Kinase Associated Protein 1 and 2) with respect to their role in TCR/CD3-mediated activation, proliferation and integrin regulation.